Proceedings of the 2014 International Conference on Advanced Mechatronic Systems 2014
DOI: 10.1109/icamechs.2014.6911560
|View full text |Cite
|
Sign up to set email alerts
|

Design of the LQR controller and observer with fuzzy logic GA and GA-PSO algorithm for triple an inverted pendulum and cart system

Abstract: In this paper, designing of the LQR controller and observer with intelligent tools for the triple inverted pendulum is investigated. Intelligent tools are considered as GA and GA-PSO optimization algorithms and fuzzy logic to qualify achieving LQR gains. The pendulum is swung up from the vertical position to the unstable position. The rules for the controlled swing up are heuristically achieved such that each swing results are controlled. The inverted pendulum and cart system are modeled and constructed their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Step 3 Construct the weighting matrices Q(t) and R(t) by substituting z δ , v δ and maximal allowable adjustment of guidance signal σ δmax into Eqs. (28), (21) and (22).…”
Section: Lqr With Time-varying Weighting Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 3 Construct the weighting matrices Q(t) and R(t) by substituting z δ , v δ and maximal allowable adjustment of guidance signal σ δmax into Eqs. (28), (21) and (22).…”
Section: Lqr With Time-varying Weighting Matricesmentioning
confidence: 99%
“…A trade-off between penalties on the state and control inputs for optimization of the cost function was considered in [25], where specified closed-loop eigenvalues were obtained, but the computation normally needed more iterations. Genetic algorithm (GA) can be applied to find a global optimal solution [26][27][28], and the differential evolution algorithms inspired from GA are efficient evolution strategies for fast optimization technique [29][30][31]. However, the approaches in [26][27][28][29][30][31] have little improvement for HSV profile-following performances under different disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…The cart-inverted pendulum is a system that usually used for testing many control algorithms [5]. There are some control algorithms that can be used for stabilising a cart-inverted pendulum such as Linear Quadratic Regulator (LQR) [6], neural network [7], genetic algorithm [8], fuzzy control [9], and PID [10] which have been studied by many researchers. The studies about the stability of a cart-inverted pendulum is very useful for developing real world application systems, for instances: a segway, an earthquake resistant building design, a human walking, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that proposed control provides faster convergence and accompanies less iterations. Molazadeh et al (2014) designed a LQR controller for control of triple inverted pendulum. The tuning of LQR gains was achieved using fuzzy logic, GA and GA-particle swarm optimisation (PSO) algorithm.…”
Section: Introductionmentioning
confidence: 99%